Pelatihan Kader Posyandu dalam Pembuatan Makanan Pendamping ASI (MP ASI) dengan Konsep Empat Bintang dalam Upaya Mendukung Tumbuh Kembang Balita - Anik Kurniawati; Rohmi Handayani (Yayasan Inspirasi El Burhani, 2023)
Introduction: Complementary breastfeeding is started from the age of 6 months with the aim of meeting the nutritional needs of infants and children apart from breast milk. The MP-ASI given according to WHO recommendations is with a menu that includes four stars. Objective: Increase the knowledge of cadres about making MP ASI with the four star concept Problem solution. Provide training for Posyandu cadres in making complementary food for ASI (MP ASI) with the four star concept in an effort to support the growth and development of toddlers Method: The methods used are lectures, discussions, demonstrations and hands-on practice of making PMBA with an expensive Result: Community service activities carried out were attended by 55 health cadres with the characteristics of the majority of cadres with middle education, more than 5 years as cadres and the majority age is over 35 years. The majority of cadres have good knowledge of PMB, increasing from 60% to 92.7%. Conclusion: Knowledge of cadres about making complementary foods with the four star concept increases, and cadres can make complementary foods practically.